PERSEPSI MASYARAKAT DESA TERHADAP PERANAN MAHASISWA KKN DALAM PEMBANGUNAN MASYARAKAT DESA (Studi di desa Gunung Rejo kecamatan Padang Cermin Kabupaten Pesawaran) - Wahyuni, Irma; Hidayati, Dewi Ayu (SOCIOLOGIE, 2013)
The primary target of Indonesia development is rural society with expectation to improve society welfare and students should play role in this activity. One of the roles is by conducting studentâs public service (or KKN). The success in conducting studentâs public service is not only depending on the studentâs performance in the society but also on public support. Therefore the public perception is very determinant in studentâs public service conduct, so that public perceptions on the studentâs public service in developing rural society needs to figure out. The objective of this research is to find out and explain the public perception on studentâs role in studentâs public service (KKN) in developing rural society based on classifications of age, occupation, and education levels. This research was conducted in Gunung Rejo village of Padang Cermin sub district in Pesawaran regency, with the majority residents of farmers with elder age and low education levels. This was a quantitative research. Samples were 27 respondents in each classification of age, occupation, and education level. Data were collected using questionnaire and interview. Data were processed with SPSS; a software of statistic data processor. The results showed that the higher education level tended to give more negative appreciation to the students. Based on occupation, unemployed people had positive perceptions to students. Farmers and civil servant had negative perceptions to students. People with older age had positive perceptions while younger people had negative perception to students.Keywords: Perception, rural society, role, student of studentâs public service program, development